Penerapan Asuhan Keperawatan pada Pasien dengan Diagnosa Medis Hipertensi di RSUD Ende - Maria Sekunda; Yustina Paschalia; Anatolia Doondori (Kelimutu Nursing Journal, 2025)
Hypertension is a cardiovascular disease with a major risk factor for global mortality. This case study aims to describe nursing care for patient Mr. I. R diagnosed with hypertension in the Internal Medicine Ward I, II of RSUD Ende. The method used is a case study approach, including assessment, nursing diagnosis, planning, implementation, and evaluation. The results showed nursing problems including acute pain, risk of ineffective cerebral perfusion, sleep pattern disturbance, and knowledge deficit. Nursing interventions were carried out over three days, with most problems partially or fully resolved. A gap between theory and practice was found, where the theory includes activity intolerance, which was not present in the real case. It is recommended that patients modify their lifestyle to be healthier and comply with pharmacological therapy